Molecular characterization of Fasciola hepatica in endemic regions of Colombia - Garcia-Corredor, Diego; Alvarado, Mateo; Pulido-Medellín, Martín; Muñoz, Marina; Cruz-Saavedra, Lissa; Hernández, Carolina; Giraldo, Julio Cesar; Vásquez-Arteaga, Luis R.; Morillo Coronado, Ana Cruz; Ramírez, Juan David (Frontiers in Veterinary Science, 2023)
Fasciola hepatica is a zoonotic trematode that affects a wide variety of hosts as cattle, sheep, and goats. In cattle, sanitary and productive impacts caused by the parasite are reflected in high worldwide economic losses. Beforehand its importance in human health was belittled, but in the past years, fascioliasis cases have been on the rise, producing an increased interest in researchers around the world. Multiple studies have been conducted using mitochondrial and nuclear markers in different geographic regions, aiming to characterize the genetic diversity of this parasite and its intraspecific variation; however, little is known about these genetic traits in South America and much less in Colombia. We collected a total of 105 adult parasites extracted from the cattle bile duct in seven Colombian departments (Antioquia, Boyacá, Santander, Cauca, Cundinamarca, Nariño, Norte de Santander, and Santander), aiming to assess the parasite’s phenotypic analyses, genetic diversity and population structure. A computer image analysis system (CIAS) was applied on the basis of standardized morphological measurements. Liver-fluke size was studied by principal component analysis (PCA). DNA sequences were obtained for nuclear markers such as the 28S, β-tubulin 3, ITS1, ITS2, and the mitochondrial marker Cytochrome Oxidase I (COI). Maximum Likelihood (ML) phylogenetic reconstructions were carried out using herein obtained sequences and sequences available in GenBank. Finally, multiple statistical tests were performed, and the parasite’s population structure was analyzed. Morphological results revealed that all the obtained individuals matched with F. hepatica’s morphology. There was no evidence of high genetic diversity, and the absence of genetic structure country-level was notorious, possibly caused by a demographic expansion of this trematode in Colombia or the low resolution of the molecular markers employed. Future studies are still needed to unveil the genetic population structure of F. hepatica across the country.